Human SNP links differential outcomes in inflammatory and infectious disease to a FOXO3-regulated pathway - Lee,JC; Espéli,M; Anderson,CA; Linterman,MA; Pocock,JM; Williams,NJ; Roberts,R; Viatte,S; Fu,B; Peshu,N; Hien,TT; Phu,NH; et al. (Cell, 2013)
The clinical course and eventual outcome, or prognosis, of complex diseases varies enormously between affected individuals. This variability critically determines the impact a disease has on a patient’s life but is very poorly understood. Here, we exploit existing genome-wide association study data to gain insight into the role of genetics in prognosis. We identify a noncoding polymorphism in FOXO3A (rs12212067: T > G) at which the minor (G) allele, despite not being associated with disease susceptibility, is associated with a milder course of Crohn’s disease and rheumatoid arthritis and with increased risk of severe malaria. Minor allele carriage is shown to limit inflammatory responses in monocytes via a FOXO3-driven pathway, which through TGFβ1 reduces production of proinflammatory cytokines, including TNFα, and increases production of anti-inflammatory cytokines, including IL-10. Thus, we uncover a shared genetic contribution to prognosis in distinct diseases that operates via a FOXO3-driven pathway modulating inflammatory responses.